Hidden in the caves: a new troglobitic species of Spaeleoleptes and the type species redescription (Opiliones, Laniatores) - Pereira, Maria Paula; Gallão, Jonas E.; Bichuette, Maria E.; Pérez-González, Abel (European Journal of Taxonomy, 2024)
The genus Spaeleoleptes was proposed by H. Soares in 1966 to accommodate the first Brazilian troglobitic species of harvestmen, Spaeleoleptes spaeleus H. Soares, 1966. In this work, we redescribe this species, including digital images of the type material and drawings of the male genitalia. Since its description, Spaeleoleptes has remained monotypic, and after 56 years, herein is described the second species of the genus, the troglobitic Spaeleoleptes gimli sp. nov. Both species share sexually dimorphic legs I and II with modified regions and swelling on the tibiae and patellae I and II; a penis with robust conductors covering all or part of the capsula interna and a capsula interna with two lateral projections. They are clearly separated by the shape of the modified region of the tibia; by the presence of an apical projection on the apical lamina of the pars distalis in S. spaeleus; and the lateral projections of the capsula interna, which is flattened in S. gimli. Spaeleoleptes gimli greatly increases the distributional range of the genus, as it is now recorded from caves located in two Brazilian phytophysiognomies from the Cerrado of Minas Gerais to the Caatinga of Bahia.